PENYULUHAN KESEHATAN MENGENAI ROKOK, GADGET DAN MENTAL ILLNESS PADA REMAJA DI KELURAHAN GUNUNG SARIK KECAMATAN KURANJI KOTA PADANG - Syafrawati syafrawati; Ahmad Hidayat; Laila Isrona; Nadya Vebrielna (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2022)
One of the adolescent behaviours that cause health problems is smoking and excessive use of gadgets. The level of cigarette use is still high in Indonesia, causing smoking behaviour to be one of the health problems in Indonesia. The prevalence of smoking among adolescents aged 10-18 years in Indonesia increased in 2018 to 9.1%. Gadget users in Indonesia are increasing. Teenagers are the age group with the highest gadget and internet users. Uncontrolled use of gadgets can cause health problems such as health problems which in turn can cause mental illness in adolescents. Gunung Sarik Village is the largest village in Kuranji District. Based on the results of the hearing with the kelurahan, it was found that the problem of teenagers there is many teenagers smoked and use gadgets. The purpose of this community service is to increase the knowledge of teenagers regarding the problems of smoking, gadgets, and mental illness. Activities carried out using health promotion methods in the form of lectures interspersed with pre-test, question and answer, and post-test and distribution of related material flayers. The results of this community service show that there is an increase in participants' knowledge of the material presented. Before health education was conducted the average knowledge of participants was 57%, after education the average knowledge was 66%. This activity has succeeded in increasing the knowledge of teenagers regarding the problems of smoking, gadgets, and mental illness, so it is hoped that in the future teenagers can avoid these behaviors.